2014
DOI: 10.1369/0022155414555145
|View full text |Cite
|
Sign up to set email alerts
|

Zonula Occludens-1, Occludin and E-cadherin Expression and Organization in Salivary Glands with Sjögren’s Syndrome

Abstract: Sjögren's syndrome (SS) is a chronic inflammatory autoimmune disorder that causes secretory dysfunction of the salivary glands leading to dry mouth. Previous studies reported that tight junction (TJ) proteins are down-regulated and lose polarity in human minor salivary glands with SS, suggesting that TJ structure is compromised in SS patients. In this paper, we utilized the NOD/ShiLtJ mouse with the main goal of evaluating this model for future TJ research. We found that the organization of apical proteins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…However, upon closer investigation we found that the tissue architecture up to 22 weeks, as determined by VH&E stains, the ECAD positive epithelial distributions and the Aqp5 + acinar, K7 + ductal, and SM α‐actin + myoepithelial populations were not obviously disrupted, including tissue areas directly adjacent to the lymphocytic infiltrations. Our observations that epithelial architecture is not significantly disrupted in the NOD/ShiLtJ mouse up to 22 weeks of age is consistent with another recent report (Mellas et al, ), and suggests that the presence of the advanced lymphocytic infiltrates may not directly disrupt the epithelium at this stage of disease progression. In the human SS affected tissues, we observed that large areas of the epithelium are disrupted surrounding the focal infiltrates and show an amorphous morphology, consistent with other reports (Goicovich et al, ; Molina et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…However, upon closer investigation we found that the tissue architecture up to 22 weeks, as determined by VH&E stains, the ECAD positive epithelial distributions and the Aqp5 + acinar, K7 + ductal, and SM α‐actin + myoepithelial populations were not obviously disrupted, including tissue areas directly adjacent to the lymphocytic infiltrations. Our observations that epithelial architecture is not significantly disrupted in the NOD/ShiLtJ mouse up to 22 weeks of age is consistent with another recent report (Mellas et al, ), and suggests that the presence of the advanced lymphocytic infiltrates may not directly disrupt the epithelium at this stage of disease progression. In the human SS affected tissues, we observed that large areas of the epithelium are disrupted surrounding the focal infiltrates and show an amorphous morphology, consistent with other reports (Goicovich et al, ; Molina et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…39 Furthermore, occludin has been shown to be expressed in acini and ducts from human minor salivary and mouse submandibular glands; 14 likewise, this protein has been found in cell lines of salivary gland origin (e.g., in polarized Par-C10 and SMIE cells). 40,91 Finally, mice lacking occludin showed loss of cytoplasmic granules in striated ducts from salivary glands, 92 suggesting that occludin may control salivary gland phenotype in both acinar and ductal structures.…”
Section: Occludinmentioning
confidence: 98%
“…Interestingly, deficiency of ZO-1 did not exert any effects on the localization of ZO-2/ZO-3 at junctional sites but did induce mislocalization of endothelial JAMs in the yolk sac, 109 which might explain the disturbance of vascular development. ZO-1 is expressed in acini, ducts, and inter-glandular endothelial cells from human major salivary glands and mouse submandibular glands 14,39,81 and is also co-localized with claudin-16 at the excretory duct of human major salivary glands. 81 ZO-1 has been used as a marker for salivary gland polarity and differentiation; 110 however, further studies are needed to determine the molecular mechanisms by which ZO-1 modulates TJs in salivary glands.…”
Section: Tight Junction Plaque Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZO‐1 and occludin form a high resistance barrier in the bladder epithelium, and deterioration of these proteins marks the disruption of the pulmonary epithelial barrier [7–10]. Studies report that in human minor salivary glands, as claudin‐1 and claudin‐4 increase, ZO‐1 and occludin decrease [11]. Additionally, the expression of the epithelial tight junction proteins ZO‐1, occludin, claudin‐1 and claudin‐2 can be regulated by brain‐derived neurotrophic factor (BDNF) [12].…”
Section: Introductionmentioning
confidence: 99%